2011
DOI: 10.1007/s00535-010-0330-5
|View full text |Cite
|
Sign up to set email alerts
|

Development of an experimental model of cholestasis induced by hypoxic/ischemic damage to the bile duct and liver tissues in infantile rats

Abstract: Reduced blood flow in the EBD during infancy induced BDPF and obstructive changes in the EBD, which may, along with immature PVP and inflammatory changes in the EBD, contribute to hypoxia/ischemia of the EBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Tissue hypoxia in the liver can be caused by several forms of liver injury . In cholestasis the toxic effect of bile acids within hepatocytes is prevented by adaptive responses such as induction of bile acid efflux transporters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue hypoxia in the liver can be caused by several forms of liver injury . In cholestasis the toxic effect of bile acids within hepatocytes is prevented by adaptive responses such as induction of bile acid efflux transporters.…”
Section: Discussionmentioning
confidence: 99%
“…Various conditions can cause hypoxia or induce hypoxia modulators, such as ischaemia, ischaemic reperfusion injury, cancer and inflammation. In addition, cholestasis induces hypoxia in the liver and low oxygen levels regulate bile salt transporters. However the exact mechanism by which hypoxia modulates the expression of these transport proteins has not been elucidated.…”
mentioning
confidence: 99%
“…Moreover, decreased hepatic blood flow and increased portal pressure due to obstruction may cause hypoxia/ischemic damage liver paranchyma and bile duct. These features may increase cholestasis as reported by previous studies [34,35]. Matsumoto et al [34] suggested that the reduction in the number of fenestrae in the liver sinusoidal endothelial cells may lead to dysfunction of the liver microcirculation in the common bile ligated rats.…”
Section: Discussionmentioning
confidence: 71%
“…Matsumoto et al [34] suggested that the reduction in the number of fenestrae in the liver sinusoidal endothelial cells may lead to dysfunction of the liver microcirculation in the common bile ligated rats. Hypoxia/ischemia in the tissue may also directly induce an inflammatory response or promote expression vascular endothelial growth factor, which causes bile duct proliferation [35].…”
Section: Discussionmentioning
confidence: 99%
“…25 We observed that UDCA-LPE prevented the loss of cIAP2 and Mcl-1 proteins known to be involved in intrinsic apoptosis. It is known that hypoxic condition in vivo can induce cholestasis 33 in part by upregulating bile acid transport genes. 34 An upregulation of cFLIP and the prevention of the loss of cIAP2 and Mcl-1 by UDCA-LPE would result in the resolution of apoptotic injury caused by hypoxia, and cholestasis at prolonger time.…”
Section: Discussionmentioning
confidence: 99%